Prediction of the Elastic Properties of the Clay-Rice Straw Composite by Numerical Homogenization Technique using Digimat - ADADJA, Christian E.; Labintan, Clément Adéoumi; GIBIGAYE, ADAM MOHAMED; ZAHROUNI, Hamid; HATTAB, Mahdia (My University, 2019)
This paper deals with numerical modelling of the elastic properties of the rice straw-clay composite. This composite material is currently attracting interest because of its low impact on the environment but also for economic reasons. Benefiting from the advantages of a promising building material, straw reinforced composites attract more attention. This work allowed to model the effect of the straw inclusions on the elastic properties of the composite by a numerical approach considering the aspect ratio, the volume fraction, the orientation and the distribution of the straw inclusions. The Mori-Tanaka homogenization scheme for the RVEs is done using Digimat-MF software and the 3D composite microstructure models are generated by the Digimat-FE software. This made it possible to calculate the effective elastic properties of the clay-rice straw composites by numerical simulation. An empirical linear correlation between the volume fraction of the inclusions and the Young's modulus has been proposed. The results obtained can help to better control the formulation of the composite in developing countries.
Keywords: Composite; Homogenization; Young’s modulus; Digimat